2021
DOI: 10.1182/blood.2020009594
|View full text |Cite
|
Sign up to set email alerts
|

Oncogene-induced maladaptive activation of trained immunity in the pathogenesis and treatment of Erdheim-Chester disease

Abstract: Trained immunity (TI) is a pro-inflammatory program induced in monocyte/macrophages upon sensing of specific pathogens and characterized by immunometabolic and epigenetic changes enhancing cytokine production. Maladaptive activation of TI (i.e., in the absence of infection) might result in detrimental inflammation and disease development; however, the exact role and extent of inappropriate activation of TI in the pathogenesis of human diseases is undetermined. Here, we reveal oncogene-induced, maladaptive indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…In LCH, BRAF V600E mutation in bone marrow progenitors gives rise to mutated clones infiltrating myeloid dendritic cells, which infiltrate virtually all tissues (16). The same mechanism is proposed in ECD with a predominant involvement of CD14+ monocytes (17) rather than dendritic cells and also an abnormal activation of "trained immunity" mediated by BRAF (18). The understanding of the brain involvement mechanism has yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In LCH, BRAF V600E mutation in bone marrow progenitors gives rise to mutated clones infiltrating myeloid dendritic cells, which infiltrate virtually all tissues (16). The same mechanism is proposed in ECD with a predominant involvement of CD14+ monocytes (17) rather than dendritic cells and also an abnormal activation of "trained immunity" mediated by BRAF (18). The understanding of the brain involvement mechanism has yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Disease activity was assessed using 18 fluorodeoxyglucose positron tomography (according to Positron Emission Tomography Response Criteria In Solid Tumors (PERCIST) criteria). Complete metabolic response was defined by the normalization of all lesions to at or below the standardized uptake value (SUV) of the liver background.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, two recent publications have explained the cause of the hyperinflammatory state in ECD and other histiocytic diseases. Molteni, R. and his colleagues found that BRAF V600E in macrophages induce hallmark immunometabolic features of trained immunity, causing activation of the AKT/mTOR signaling axis, increased glycolysis, epigenetic changes on promoters of genes encoding cytokines, and enhanced cytokine production leading to hyper-inflammatory responses [ 14 ]. Biavasco, R. and his colleagues discovered that the activation of BRAF V600E impairs HSPC function, features myeloid restricted hematopoiesis, and leads to a widespread inflammatory condition [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, simulated microgravity influenced metabolic pathways, such as lipid metabolism and the Krebs cycle in human breast cancer cells, osteoblasts, oligodendrocytes and gastric cancer cells (51)(52)(53)(54). Of note, metabolomic analysis of supernatants of Erdheim-Chester disease (ECD) biopsies cultured for 4 days in RCCS Bioreactor revealed that the immunometabolic changes of trained immunity occurring in ECD lesions in vivo, such as increased glycolysis and accumulation of fumarate and malate, can be dampened by MAPK pathway inhibition (55). A recent study in gastric cancer showed that PDE culture in RCCS bioreactor recapitulates the action of chemotherapy in patients by affecting cell survival and by weakening the action of drug resistanceassociated genes (56).…”
Section: Patient-derived Models For Cancer Drug Testingmentioning
confidence: 99%